Retrospective Review of Information Technologies in the Criminal Code of Kazakhstan - AKHMETOV, Aibek T.; BEKISHEVA, Sabigul D.; SYRBU, Aleksandr V.; KAINAZAROVA, Dariga B. (Journal of Advanced Research in Law and Economics, 2018)
It is currently impossible to imagine the improvement of some sphere without modern technologies. The president of Kazakhstan, Nursultan Nazarbayev in the Presidential Message to the people underlines the need in the wide introduction of the elements of the Fourth Industrial Revolution. The objective of the paper is to analyze the retrospective review of the information technologies in the Criminal Code of Kazakhstan. As the method studying the research subject, we use the analysis of the criminal procedure legislation, digital programs, as well as the opinion of the scientists and specialists regarding the possibility of the introduction and use of the information technologies in the activities of the judicial authorities. A series of scientists prefer new progressive technologies in the criminal court processing, including the electronic criminal case. Besides, the programs dedicated to the development of the court system in Kazakhstan contain a series of prerequisites forcing the court reform to introduce the electronic base of the criminal case.